Symmetrized Maxwell–Garnett Approximation as an Effective Method for Studying Nanocomposites - M. M. Yashin; H. B. Mirzokulov (Российский технологический журнал, 2019)
The symmetrized Maxwell-Garnett (SMG) approximation is considered as the most optimal method of an effective medium for the description of nanocomposite structures. This approximation takes into account the microstructure of the sample, which makes it possible to calculate the metal-dielectric system. Thus, SMG describes with good accuracy the structure of the nanocomposite. Besides, this approximation is applicable for granular alloys consisting of metal components. As a result, this technique can be considered as a universal approximation to describe a wide class of nanostructured materials. At the same time, this article discusses various methods of effective environment. In these methods, the metal component of nanocomposites and the dielectric matrix are replaced by an effective medium with effective permittivity εeff. It is necessary that the particles (granules) in such structures be small in comparison with the wavelength of electromagnetic radiation incident on the sample. Based on this, the spectral dependences of the transverse Kerr effect (TKE) in magnetic nanocomposites were calculated with (CoFeZr)(Al2O3) structure as an example at different concentrations of the magnetic component. The simulation was carried out at small and large concentrations (below and above the percolation threshold). The spectral dependences were obtained taking into account the form factor of nanoparticles and the quasi-classical size effect. Besides, the authors note and discuss in this paper the contribution of various mechanisms that affect the type of spectra of the transverse Kerr effect. Using the symmetrized Maxwell-Garnett approximation, the effective values of the granule size of the nanocomposites under study were found, and the tensor of effective dielectric permittivity (TEDP) was calculated. The obtained TEDP values allowed to simulate the spectral dependences of the magneto-optical transverse Kerr effect. The authors discuss and draw conclusions about the features of the obtained spectral dependences in both the visible and infrared regions of the spectrum. In addition, the practical and fundamental importance of the obtained results is noted. The importance of effective medium methods for the study of optical, transport and magneto-optical properties of magnetic nanocomposites is shown.